Eksplorasi Kualitas Hidup Remaja dengan Obesitas: Studi Kualitatif: Exploration of Quality of Life among Adolescents with Obesity: a Qualitative Approach - Rakhmawati Agustina; Cut Mutiya Bunsal (Amerta Nutrition, 2025)
Background: Quality of life represents a person's perception of satisfaction and significance in life. Obese adolescents are a vulnerable group because they frequently encounter social stigma and prejudice. This issue affects not only their physical health, but also their self-esteem and the quality of their social relationships. Objectives: This study aims to explore the quality of life experiences of obese adolescents. Methods: The study used a qualitative design with a case study approach, conducted at Muhammadiyah Manado High School from February to May 2025.  Data were collected through in-depth interviews with five important informants, which included interview guidelines, documentation, and a voice recorder. Triangulation was accomplished by in-depth interviews with six supporting informants (family, close friends, and teachers). Data were thematically processed using the Non-Versioned Information, Versatile Outcomes (NVIVO) 15 software. Results: The analysis found that obese adolescents' quality of life is divided into 5 themes: (1) the effects of obesity (physical and psychological), (2) feelings and self-image (negative emotions and social stigma), (3) lifestyle (diet and physical activity), (4) the influence of social media (sources of pressure and information), and (5) strategies for overcoming obesity. Conclusions: Obese adolescents' quality of life is determined by the interaction of physical and psychological conditions, lifestyle, and social support or obstacles, but the right strategy can help to improve the situation while also building self-resilience in facing the stigma and challenges experienced.